No flood effect on recruitment in a Louisiana black bear population. Issue 3 (17th November 2017) - Clark, Joseph D.; O'Connell‐Goode, Kaitlin C.; Lowe, Carrie L.; Murphy, Sean M.; Maehr, Sutton C.; Davidson, Maria; Laufenberg, Jared S.
ABSTRACT: A flood event in 2011 had minor impacts on apparent survival and movement probabilities of a small, isolated population of Louisiana black bears ( Ursus americanus luteolus ) in the Upper Atchafalaya River Basin, Louisiana, USA. However, the potential effects of the flood on recruitment of juveniles into the population, then listed as threatened under the United States Endangered Species Act, were not evaluated. We used hair trapping data collected from 2007 to 2015 and Pradel temporal symmetry models in a robust‐design framework to investigate changes in per capita recruitment that could have resulted from the flood. We detected 91 bears (37 M:54 F) within the flooded area during our study period, ranging from 21 to 44 individuals/year. Models that tested for reduced recruitment resulting from the flood were not supported more than models with constant recruitment, and the population growth rate did not decline. Although we documented marginally lower recruitment following the 2011 flood, lag effects and detectability biases complicated our analysis. We suggest that wildlife managers continue monitoring recruitment and survival in this recently delisted black bear population given the potential for heightened flood frequency and severity in the future. © 2017 The Wildlife Society. Abstract : Using capture‐mark‐recapture hair trapping data from 2007 to 2015 and Pradel temporal symmetry models, we investigated potential changes in Louisiana black bear ( Ursus americanus luteolus ) recruitment because of a flooding event that occurred in 2011 in the Upper Atchafalaya River Basin, Louisiana, USA. Hypotheses of reduced recruitment were not supported and population growth probabilities did not decline but we suggest that wildlife managers continue monitoring this recently delisted black bear population given the potential for heightened flood frequency and severity in the future.